ANALYSIS OF PALM OIL BIOMASS UTILIZATION FOR RENEWABLE ENERGY GENERATION AT PTPN IV DOLOK ILIR - Fitri Annisa Alfi Siregar,; Effendi, Zulham (Jurnal Silva Samalas, 2026)
This study analyzes the potential and utilization of palm oil biomass as a renewable energy source in the cogeneration system of PTPN IV Dolok Ilir, North Sumatra. Palm oil processing generates three primary biomass residue streams: empty fruit bunches (EFB, 22-23% w/w of FFB), mesocarp fiber (12-13% w/w of FFB), and palm shells (5-6% w/w of FFB). The installed cogeneration capacity is 2,000 kW; however, operational observations in August 2025 recorded an average actual power output of 746 kW (37.3% of installed capacity). Turbine isentropic efficiency averaged approximately 55.81%, compared to a design value of 75.00%, indicating a gap of 19.19 percentage points. Steam mass flow rates averaged 42.4 t/h against a design value of 64.9 t/h. EFB, the largest residue stream by weight, remains underutilized as cogeneration fuel. The findings highlight significant opportunities to enhance biomass-to-energy conversion through maintenance optimization and EFB valorization strategies.